Estimation level of public welfare on the basis of methods of intellectual analysis - S. Kozlovskyi; L. Nikolenko; O. Peresada; O. Pokhyliuk; O. Yatchuk; N. Bolgarova; O. Kulhanik (Global Journal of Environmental Science and Management)
In the context of globalization of economic development processes, the issue of determining the level of public welfare of economic agents is particularly burning. The object of ehis study is the process of assessing welfare of the economic entities system. The subject of the study is the instrumental and mathematical aspects of modeling and measuring the public welfare. The aim of the work is to develop the mathematical model for measuring the welfare of Ukraine using methods of intellectual analysis, namely, the theory of fuzzy sets. The output of the study is a new approach to objective estimation of public welfare of the state. It is proposed to assess the level of public welfare of the state on the basis of a mathematical model developed on the basis of the theory of fuzzy sets. Input factors of the model are international indices and indicators, such as Index of Economic Freedom, Global Peace Index, Democracy Index, Corruption Perceptions Index, Human Development Index, Prosperity Index, Global Competitiveness Index as well as an indicator that reflects the characteristic property of the Ukrainian economy, namely the minimum living wage. Developed mathematical model for assessment of the level of public welfare of Ukraine and made a prediction of the indicator by 2024 on the basis of the above indices. The results of the study allowed us to establish that the level of public welfare (units) in Ukraine on a scale from 0 to 100 will be equal to 25, 17, 32, 26, and 28 in 2020, 2021, 2022, 2023, and 2024, accordingly.